Gone to Texas: phylogeography of two Trachymyrmex (Hymenoptera: Formicidae) species along the southeastern coastal plain of North America. (March 2015) - Seal, Jon N.; Brown, Larrimy; Ontiveros, Cynthia; Thiebaud, Jeffrey; Mueller, Ulrich G.
<x xml:space="preserve">Abstract</x> Ants are widely recognized as ecologically important members of many low‐ to mid‐latitude ecosystems. Surprisingly, there is very little phylogeographical information on ants at regional scales. We examine here the phylogeography of two partially sympatric species of Trachymyrmex (Trachymyrmex septentrionalis and Trachymyrmex turrifex) ants in southeastern North America. We test the hypothesis that all Trachymyrmex species found in the USA expanded into North America from refugial populations located in northern Mexico as the post‐Pleistocene climate warmed. Phylogeographical theory predicts that these northward‐expanding species should exhibit higher genetic diversity in regions closer to Mexico and less diversity in more northern regions. We also examine, in the widely distributed T. septentrionalis, the hypothesis of vicariance that occurred at the formation of the Mississippi Embayment. Phylogeographical patterns indicate that T. septentrionalis has an eastern origin because diversity was highest east of the Mississippi, whereas T. turrifex probably has a Mexican origin because it lacked mitochondrial DNA (mtDNA) variation throughout its range and is currently absent from eastern North America. Both species are characterized by reduced haplotypic variation in the western coastal plain of the Gulf of Mexico (Texas and Louisiana), which may indicate recent expansion and/or bottlenecks associated with increased aridity and drought in these western regions. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 114, 689–698.